Detection of anti-ebolavirus antibodies in Ghanaian pigs - OGAWA, Hirohito; OHYA, Kenji; AYIZANGA, Raphael; MIYAMOTO, Hiroko; SHIGENO, Asako; YAMADA, Masao; TAKASHIMA, Yasuhiro; INOUE-MURAYAMA, Miho; TAKADA, Ayato; KAYANG, Boniface BABOREKA (Journal of Veterinary Medical Science, 2022)
Some filoviruses such as ebolaviruses and marburgviruses, cause hemorrhagic fever in humans and nonhuman primates. Pigs are suggested to play a potential role in the filovirus ecology. We investigated the seroprevalence of filovirus infection in pigs in Ghana. Using a viral glycoprotein (GP)-based enzyme-linked immunosorbent assay, we detected filovirus-specific immunoglobulin G antibodies in 5 of 139 samples. These positive sera showed specificities to four different filovirus species. Particularly, two of the positive sera reacted to GPs of two African ebolaviruses (i.e., Ebola virus and Taï Forest virus) in Western blotting. Our results suggest that these Ghanaian pigs were exposed to multiple filoviruses and emphasize the importance of continuous monitoring of filovirus infection in pig populations in West African countries.